Juridical Analysis of Interim Decisions in Cases of Embezzlement in Office: Case Study of Decision Number 664/Pid.B/2013/PN.Jkt.Sel. - Kartiko, Nafis Dwi (Journal of Legal and Cultural Analytics, 2024)
This research focuses on the juridical analysis of interlocutory decisions in cases of embezzlement in office, with a case study of RD. Yudi Suyud Indriardi and PT Employee Cooperative. Indonesian post. Existing studies generally take a normative approach to the regulation of legal processes, but are still limited in providing analysis of the application of these laws in actual judicial practice. This research aims to fill this gap by providing a more concrete analysis and possible solutions to the inconsistencies that exist in interlocutory decisions. The research method used is a normative juridical approach using primary and secondary legal materials. In-depth and focused research on cases such as RD Yudi Suyud Indriardi will produce new insights regarding the application of Article 143 of the Criminal Procedure Code which aims to strengthen the legal basis of judges' decisions and guarantee the rights of defendants. This research makes a significant contribution to theoretical understanding and practical application in the justice system. By examining cases and court decisions, this research contributes to the enrichment of existing legal literature by providing an in-depth analysis of the extent to which judges' considerations influence the validity and quality of decisions. From a practical perspective, this research demonstrates the need for precision in the writing and formulation of indictments and judge's decisions, which must meet the standards set by law. This research also emphasizes the importance of better understanding of Article 143 of the Criminal Procedure Code among legal practitioners.